2017
DOI: 10.1111/wej.12255
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of water reserves in mineral soils with different retention properties

Abstract: This work focuses on modelling soil water reserves using an Artificial Neural Network (ANN). Four model variants were established based on 843 records (verified through 268 measurements) of soil water content (SWC) measured at full-scale field sites located in Southwest Poland. It is revealed that commonly recorded climatic data (precipitation and temperature) linked with SWC and field water capacity (FWC) are applicable in the ANN modelling. The basic model (utilising the meteorological data) was the most sui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…The evaluation was completed based on summing up the points scored for each soil thickness, as presented in Table . The ranking analysis revealed that the best accuracy (top score with 7 ranking points) for each of the three soil thicknesses was defined by three different model variants, and two of them were the newly developed models E and G. Yet, the basic model D was the most accurate for the middle thickness of the soil profile (0–50 cm), which corresponds with findings of the previous studies (Orzepowski et al ). In the deepest layer (0–100 cm), the top rating was achieved for model E, which exchanges the variable SWC in model D with GWT position measured at the beginning of the growing season.…”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…The evaluation was completed based on summing up the points scored for each soil thickness, as presented in Table . The ranking analysis revealed that the best accuracy (top score with 7 ranking points) for each of the three soil thicknesses was defined by three different model variants, and two of them were the newly developed models E and G. Yet, the basic model D was the most accurate for the middle thickness of the soil profile (0–50 cm), which corresponds with findings of the previous studies (Orzepowski et al ). In the deepest layer (0–100 cm), the top rating was achieved for model E, which exchanges the variable SWC in model D with GWT position measured at the beginning of the growing season.…”
Section: Resultssupporting
confidence: 85%
“…For this purpose, combinations of the results of the measured and estimated data applied in the most comprehensive model G and in the initial model A (relying only on the basic climatic data) were compared. This particular combination was justified as the most reliable for the data comparison for two reasons: 1 -the present study revealed that model G is the most accurate (7 ranking points) only in the most upper soil layer (0-25 cm), 2 -the former studies by Orzepowski et al (2017) defined variant A as highly suitable (6 ranking points) for modelling in the shallowest soil layer. Results of the comparison are exemplified by water contents in the uppermost layer of soil profile Sm through the last six growing seasons (GS1-GS6, Fig.…”
Section: Resultsmentioning
confidence: 62%
See 3 more Smart Citations